Do characteristics of family members influence older persons' transition to long-term healthcare services? - Astri Syse; Alyona Artamonova; Michael Thomas; Marijke Veenstra (BMC, 2022)
Abstract Background Future demographic and economic changes warrant a better understanding of older persons' need for health-related long-term care services (LTC). LTC uptake among older people is likely to be influenced by the presence or absence of family members, but there is scarce research on the role played by partners with different caregiving potential. There is even less research on the contributions of adult children and their caregiving potential. The current study examines the extent to which transitions into LTC in older men and women differ according to the presence and caregiving potential of partners and children. Methods Linked registry data for Norway on older persons (aged 65+), their partners, and their adult children are used to examine how characteristics of these family members influence transitions into LTC from 2010 to 2016, using logistic discrete-time hazard regression models. We observed around 215,000 transitions to LTC, corresponding to around 26.3% of individuals and 5.4% of the total person-years (4.0 million). Caregiving potential is measured in terms of employment, income, health and educational attainment for partners and education and geographical proximity for children. Results Personal, partner and child(ren)'s resources are all associated with older persons' LTC uptake. Unpartnered and/or childless older people are more likely to use LTC than those with partners and/or child(ren). Older persons with resourceful partners and children are the least likely to transition into LTC. The geographical proximity of adult children appears to have only a minor influence on LTC use among older people. Conclusions Population ageing and strained public resources will likely challenge the future provision of formal old-age care. The role of family networks in the future provision of formal old-age care is expected to become progressively important in the years to come. Inequalities in the health, care and welfare of older persons with and without resourceful family members are likely to increase.